Test of CAPM in China Stock Market - Chen, Xin (2006)
In this dissertation some representative historical empirical tests of CAPM are reviewed. Then we examine the validity of the CAPM from the year 2001 to 2005 for Shanghai Stock Exchange, which is one of the two stock markets in mainland China. Using the methodology of Fama and MacBeth (1973), I find that the market beta does not seem to play a significant role in explaining the cross-sectional returns, which is inconsistent with the conclusion of the previous research reached by Fama and MacBeth. However, it should be addressed that all the empirical tests of CAPM including the one that has been done in the dissertation may face some inevitable criticism such as the doubt in whether the CAPM is testable.